أسلوب كايـــزن وعلاقتــه بتخفيض التكاليف (Journal of Accounting and Financial Studies ( JAFS ), 2010)
The world is witnessing now big developments in the technological sphere These developments have led to the emergence of fierce competition among enterprises and competition had become the most important cross-cutting cost, which in turn reflected in the selling prices and profit . Based on that have emerged in recent years, techniques and new management methods in order to keep pace with these changes and developments in the business environment, although these techniques came to meet the needs of management of the Department of mandated and reduced so as to realize customer satisfaction, including the method of Kaizen, as is the idea that the philosophy of continuous improvement - even it is simple - a whole has the net effect than the total of those improvements without having to bear any costs high. The process of improvement of people, processes, equipment, materials, labor and production  methods and the process is completed through the great support from senior management.The research dealt with three topics: the first included the theoretical side, which dealt with a portal to the definitions of method and Kaizen techniques. The second topic dealt with the practical aspects of this method in the company's research sample. In the third part, it included the most important conclusions and recommendations reached in the research.